Cognitive Semantic Study of the Preposition ‘Min’ in the Quran - Khan, Sardaraz; Syed Naeem Badshah; Khan, Irfan Ullah (Journal of Islamic and Religious Studies, 2019)
The preposition ‘min’ is semantically more complex than what the traditional lexicaAl-syntactic approaches held it to be adverb or adverbial of place and time. This paper attempts to investigate the semantic complexity of the preposition ‘min’ from cognitive linguistic perspective to find out its semantic classification and linguistic symmetric patterns. Data has been taken from the Quran to investigate the claim of conceptual metaphor theory that sensorimotor neural structures generates the preposition ‘min’ on the image schema of source-path-goal. The findings reveal that the source-pathgoal image schema is not only at work in the use of preposition ‘min’ in spatio-geometric sense, but also to map the abstract concepts, emotional states and relationship with supernatural entities in spatial terms in the Quran. However, the data also show idiosyncratic behaviour of preposition, attaining different semantic arguments in different linguistic contexts, which strengthen the argument that language use cannot be abridged to static mapping in the human conceptual system. This paper recommends future research on the same preposition or other prepositions to investigate further the source-path-goal image schema in the Quran and Arabic language.